The Effect Of Consumptionambon Banana On Blood Pressure And Pulse Rate In Menopausal Women At Karang Anyar Rt. 49, Tarakan City, North Kalimantan - Siti Komariyah; Suberly (Universitas STRADA Indonesia, 2026)
Hypertension is a non-communicable disease that often occurs in menopausal women due to hormonal changes and decreased blood vessel elasticity. One non-pharmacological therapy that can be used to help lower blood pressure is consuming Ambon bananas because they contain high levels of potassium and magnesium. This study aims to determine the effect of Ambon bananas on blood pressure and pulse in menopausal women with hypertension in Karang Anyar Village, RT. 49, Tarakan City, North Kalimantan. The study used a quasi-experimental design with a one-group pretest-posttest approach. The study population was 79 menopausal women with hypertension with a sample of 44 respondents selected using simple random sampling. Data were collected using blood pressure and pulse observation sheets, then analyzed using the Wilcoxon test. The results showed that before the intervention, most respondents had moderate blood pressure (84.1%), while after the intervention, most were in the normal category (70.5%). Pulse rates before the intervention were mostly normal (63.6%) and after the intervention increased to 91%. Statistical test results showed a significant difference in blood pressure of p=0.000 and pulse rate of p=0.046, indicating that Ambon bananas have an effect on blood pressure and pulse rate in menopausal women with hypertension. The potassium and magnesium content in Ambon bananas plays a role in helping vasodilate blood vessels and maintain stable heart function. Consuming Ambon bananas can be used as an alternative non-pharmacological therapy to help control hypertension in menopausal women.